2001
DOI: 10.1007/s004420000607
|View full text |Cite
|
Sign up to set email alerts
|

Prey availability limits fecundity and influences the movement pattern of female fishing spiders

Abstract: We conducted a food supplementation field experiment to test two hypotheses: (1) fecundity of the fishing spider Dolomedes triton is limited by a shortage of prey, and (2) the increased movement of adult female D. triton exhibited upon maturation is a foraging adaptation to lessen the impact of food limitation on egg production. Free ranging, uniquely marked adult female fishing spiders were assigned either to a food-supplemented group that received crickets in addition to their natural diet, or to a control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 44 publications
1
73
0
Order By: Relevance
“…Second, higher dispersal activity in the scarcely vegetated grey dunes may be due to a lack of suitable prey, such as epigeic springtails and diptera unpublished data). Likewise, Kreiter and Wise (2001) showed increased mobility in the absence of suitable prey for American populations of the fishing spider (Dolomedes triton). Female spiders live 2-3 months longer than their male conspecifics and are founders.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, higher dispersal activity in the scarcely vegetated grey dunes may be due to a lack of suitable prey, such as epigeic springtails and diptera unpublished data). Likewise, Kreiter and Wise (2001) showed increased mobility in the absence of suitable prey for American populations of the fishing spider (Dolomedes triton). Female spiders live 2-3 months longer than their male conspecifics and are founders.…”
Section: Discussionmentioning
confidence: 98%
“…butterflies: Harrison et al 1988, Thomas andHarrison 1992, Thomas et al 1992;grasshoppers: Hjerman and Ims 1996, Appelt and Poethke 1997, Kuhn and Kleyer 2000. Few studies have dealt with dispersal of spiders, except for some larger Pisauridae species (Kreiter and Wise 2001). Spiders can disperse in two distinct ways: either by cursorial movement (mainly adults) or by aerial ballooning (restricted to juveniles for the larger species).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown that spiders frequently encounter periods of prey shortage and have suggested that many spiders are energy limited in nature (Anderson 1974;Wise 1979Wise , 1993Miyashita 1992;Kreiter and Wise 2001;reviewed in Wise 2006). The prey available to a colony will vary in nutritional composition, thus affecting the availability of different nutrients to colony members (Barker et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Because body size of adult spiders is to a high degree determined by food supply during pre-adult development (e.g., Uetz et al, 2002) and female body size is a major determining factor of fecundity (Beck & Connor, 1992;Kreiter & Wise, 2001) we further hypothesize that P. agrestis individuals are larger and females more fecund in complex landscapes that offer more refuges and/or prey than structurally poor landscapes.…”
Section: Introductionmentioning
confidence: 99%